Phosphate Favors the Biosynthesis of CdS Quantum Dots in Acidithiobacillus thiooxidans ATCC 19703 by Improving Metal Uptake and Tolerance - Ulloa, Giovanni; Quezada, Carolina P.; Araneda, Mabel; Escobar, Blanca; Fuentes, Edwar; Álvarez, Sergio A.; Castro, Matías; Bruna, Nicolás; Espinoza-González, Rodrigo; Bravo, Denisse; Pérez-Donoso, José M. (Frontiers in Microbiology, 2018)
Recently, we reported the production of Cadmium sulfur (CdS) fluorescent semiconductor nanoparticles (quantum dots, QDs) by acidophilic bacteria of the Acidithiobacillus genus. Here, we report that the addition of inorganic phosphate to Acidithiobacillus thiooxidans ATCC 19703 cultures favors the biosynthesis of CdS QDs at acidic conditions (pH 3,5). The effect of pH, phosphate and cadmium concentrations on QDs biosynthesis was studied by using Response Surface Methodology. To address how phosphate affects intracellular biosynthesis of CdS QDs, the effect of inorganic phosphate on bacterial cadmium-uptake was evaluated. By measuring intracellular levels of cadmium we determined that phosphate influences the capacity of cells to incorporate cadmium. A relation between cadmium tolerance and phosphate concentrations was also determined, suggesting that phosphate participates in the adaptation of bacteria to toxic levels of this metal. In addition, QDs-biosynthesis was also favored by the degradation of intracellular polyphosphates. Altogether, our results indicate that phosphate contributes to A. thiooxidans CdS QDs biosynthesis by influencing cadmium uptake and cadmium tolerance. These QDs may also be acting as a nucleation point for QDs formation at acidic pH. This is the first study reporting the effect of phosphates on QDs biosynthesis and describes a new cadmium-response pathway present in A. thiooxidans and most probably in other bacterial species.